Pengaruh Polymorphisme PvuII Gen Reseptor Estrogen Alfa terhadap Kadar Kalsium dan Phosphat Serum pada Wanita Postmenopause - Prasetyastuti Prasetyastuti (Berita Kedokteran Masyarakat (BKM), 2010)
Background: Estrogen has an important role in bone metabolism. The hypoestrogenemia condition occurring in postmenopausal women may affect bone metabolism. The mechanism action of estrogen to prevent the activity of osteoclast in bone resorption was mediated especially by estrogen receptor alpha gene (ESR1). The PvuII polymorphism that occurs in ESR1 gene may alter their expression and  function.Objectives: the aim of this research was to determine the difference of serum calcium and phosphate level in postmenopausal women with PvuII polymorphism of the Estrogen receptor alpha geneMethod: This was cross sectional design. The subjects are postmenopausal women 50-70 year old .Twenty seven subject divided into two group, group I consisted of 15 women with genotype PP,Pp and group II consisted of 12 with genotype pp. polymorphism were assessed by Polymerase Chain Reaction Restriction Fragmen Length Polymorphism(PCR-RFLP) technique. Determination of serum calcium and phosphate level used spectrophotometer. The data was analyzed with Independent sample t-test.Results: The serum calcium level are 8,15 ± 1,35 mg/dl and 8,13 ± 1,58 mg/dl in genotype PP,Pp and pp respectively. The serum phosphate level are 3,8 ± 0,47 mg/dl and 4,24 ± 0,86 mg/dl in genotype PP,Pp and pp respectivelyConclusion: there were no statistically significant differences in serum calcium and phosphate level among genotype PP,Pp with pp  ESRI gene(p>0,05) PvuII polymorphism of ESRI gene did not influence serum calcium and phosphate level in postmenopausal women.Keywords: postmenopausal women, estrogen receptor polymorphism, serum calcium, serum phosphate